Between sex and fright. Augustus and literature, or a Non-Academic History of the first emperor of Rome - García Jurado, Francisco (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2017)
The aim of this study is to lay the foundations of what would be a “Non-Academic History” (NAH) of the figure of Octavius Augustus in modern literature and essay, essentially since the second half of the 19th century, according to three essential parameters:a) The NAH is not a programmatic History, but something that happens spontaneously in diverse literary manifestations.b) We are faced with personal inquiries, more typical of elaborate hermeneutics than a factual investigation based on “sources”.c) The NAH is articulated through “tensions”, such as regeneration in the face of decadence, or fear in the face of happiness. Moreover, the literary character of the emperor is subject to tensions with respect to various historical figures, such as other emperors, contemporary poets and the figure of Christ himself.In this way, and according to the above, the most important recreations of the figure of Augustus and his political work will appear in relation to other characters, as is the case of Virgilius. To illustrate this “Non-Academic History”, I will draw on three significant authors who belong to quite different times: the anarchist thinker Pierre Joseph Proudhon, the novelist Hermann Broch and the essayist Pascal Quignard.
Keywords: Octavius Augustus; Non Academic History